Academic Procrastination, Task Values, and Self-Efficacy of Pre-Service Biology Teachers in Online Learning Based on a Gender Perspective - Astutik, Fuji; Tauhidah, Dian; Rofi'ah, Ndzani Latifatur; Adi, Widi Cahya; Saefi, Muhammad (Universitas Negeri Jakarta, 2024)
Online learning can contribute to increased academic procrastination, often linked to low self-efficacy and perceived task value. This study investigates academic procrastination, self-efficacy, and task values from a gender perspective using a cross-sectional approach with students in their 1st, 3rd, 5th, and 7th semesters. An independent t-test assessed differences between male and female students. Findings showed no significant differences in academic procrastination across genders in any semester; however, notable differences in self-efficacy and task value emerged only in the 5th semester. The lack of significant differences in procrastination is attributed to similarities in environmental, psychological, and social factors, alongside common challenges in time management and distractions. Male and female students demonstrated comparable self-efficacy due to shared academic settings, social support, and media influences, while similar task values stemmed from common interests and experiences. The differences in the 5th semester likely arise from increased academic demands and evolving social dynamics, including gender stereotypes. Future research should employ qualitative methods, such as interviews or focus groups, to gain deeper insights into student experiences. Longitudinal studies could also track changes in self-efficacy and task value over time for a more comprehensive understanding. Targeted interventions to enhance self-efficacy and task value could be particularly beneficial in semesters with significant differences, thereby addressing academic procrastination more effectively.